Rapid and Stable Microbial Community Assembly in the Headwaters of a Third-Order Stream - Teachey, Morgan E. (Appl Environ Microbiol, 2019)
Small streams and their headwaters are key sources of microbial diversity in fluvial systems and serve as an entry point for bacteria from surrounding environments. Community assembly processes occurring in these streams shape downstream population structure and nutrient cycles. To elucidate the development and stability of microbial communities along the length of a first- through third-order stream, fine-scale temporal and spatial sampling regimes were employed along McNutt Creek in Athens, GA, USA. 16S rRNA amplicon libraries were constructed from samples collected on a single day from 19 sites spanning the first 16.76 km of the stream. To provide context for this spatial study and evaluate temporal variability, selected sites at the stream’s upper, mid, and lower reaches were sampled daily for 5 days preceding and following the spatial study. In a second study, three sites at and near the creek’s headwaters were sampled daily for 11 days to understand initial bacterioplankton community assembly. Both studies revealed decreasing alpha and beta diversity with increasing downstream distance. These trends were accompanied by the enrichment of a small fraction of taxa found at low abundance in headwater-proximal sites. Similar sets of taxa consistently increased in relative abundance in downstream samples over time scales ranging from 1 day to 1 year, many of which belong to clades known to be abundant in freshwater environments. These results underpin the importance of headwaters as the site of rapid in-stream selection that results in the reproducible establishment of a highly stable community of freshwater riverine bacteria. IMPORTANCE Headwater streams are critical introduction points of microbial diversity for larger connecting rivers and play key roles in the establishment of taxa that partake in in-stream nutrient cycling. We examined the microbial community composition of a first- through third-order stream using fine-scale temporal and spatial regimes. Our results show that the bacterioplankton community develops rapidly and predictably from the headwater population with increasing total stream length. Along the length of the stream, the microbial community exhibits substantial diversity loss and enriches repeatedly for select taxa across days and years, although the relative abundances of individual taxa vary over time and space. This repeated enrichment of a stable stream community likely contributes to the stability and flexibility of downstream communities.